2011
DOI: 10.1159/000324428
|View full text |Cite
|
Sign up to set email alerts
|

Haemodiafiltration Does Not Reduce the Frequency of Intradialytic Hypotensive Episodes when Compared to Cooled High-Flux Haemodialysis

Abstract: Introduction: Intradialytic hypotension remains the commonest complication of outpatient haemodialysis (HD) treatments. On-line haemodiafiltration (HDF) has been reported to reduce the frequency of intradialytic hypotension. We introduced on-line HDF into our satellite dialysis program, and prospectively audited the effect of HDF on cardiovascular stability. Methods: 34 patients’ dialysis schedules (Tuesday/Thursday/Saturday) were converted to online post-dilutional HDF, and 44 patients’ dialysis schedules (Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 54 publications
2
28
1
3
Order By: Relevance
“…Patients treated with HDF reported fewer symptoms than those on HD, apart from hypotension and the time to recover after the treatment. Previous reports have shown an advantage of HDF in reducing intra-dialytic hypotension [10], although later studies have shown no benefit when using cooled dialysate [22], as with our cohort. However, as most of our centres predominantly used one dialysis modality, our findings could be affected by centre effects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Patients treated with HDF reported fewer symptoms than those on HD, apart from hypotension and the time to recover after the treatment. Previous reports have shown an advantage of HDF in reducing intra-dialytic hypotension [10], although later studies have shown no benefit when using cooled dialysate [22], as with our cohort. However, as most of our centres predominantly used one dialysis modality, our findings could be affected by centre effects.…”
Section: Discussionsupporting
confidence: 51%
“…We have traditionally used cooled dialysate to reduce the frequency of intra-dialytic hypotension [22]. Although very few patients actively complained to supervising nursing or medical staff about feeling cold, most patients reported feeling cold during treatment, and there has been a debate regarding the benefits of isothermic compared to cooled dialysate in terms of reducing intra-dialytic hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly on-line HDF has been reported to lead to greater cardiovascular stability and reduced intradialytic hypotension compared to standard HD [4], although other smaller studies did not find a difference in intradialytic hypotension and dialysis mode [15], particularly when comparing HDF with HD using cooled dialysate [16]. …”
Section: Discussionmentioning
confidence: 99%
“…2 Some, if not all, of the increased tolerability of hemodiafiltration may be due to thermal effects. 9 Use of lower-temperature dialysate has been associated with reduced cardiovascular mortality, 10 and it is possible that some of the "hard outcomes" benefits of high-volume hemodiafiltration in terms of fewer cardiovascular events may be due to slight cooling associated with this therapy. Use of pharmacologic aids to maintain BP during dialysis, such as midodrine or sertraline, have no additive benefit if given to patients being dialyzed with cool-temperature dialysate.…”
mentioning
confidence: 99%